O vôo do pássaro e seu canto: trajetória de um espírita e do Espiritismo em Feira de Santana (1940-1960) - Morgado, Chablik de Oliveira (2015)
This work aims to understand the trajectory of alagoinhense Osvaldo Pinheiro Requião, the establishment of Spiritualism in Feirense religious field during the decades 1940-1960, and as the central axis of analysis their engagement in Feirense spiritual movement. Arriving in Feira de Santana to work as a prosecutor, Spiritualism had already given its first steps in the city. In it, Osvaldo Requião has also worked as a teacher of Portuguese Language in that period, having built up a network sociability that allowed its insertion in different spaces from city prestige, such as the Folha do Norte newspaper; Rotary Club of Feira de Santana; the Colégio Santanópolis and Escola Normal. His performance was mainly through the column À vol d'oiseau at between the 1950s to early 1960s, dedicated almost in full to the spread of Spiritualism. Among the controversies that Requião was involved it is worth mentioning the Religious Education, which criticized the catechetical model employed in the public schools of Feira de Santana. One cannot say that the conversion route the performance of Osvaldo Requião to Spiritualism followed a linear trajectory. The son of a Protestant and a spiritualist, Osvaldo Requiao not become adept Spiritualism would be atheist, period of its history marked by the reading of books devoted to denying the existence of Jesus. With his conversion, from reading The Book of Spirits, it has acted in favor of disclosure of Spiritualism in the cities where he went as a prosecutor, like Castro Alves, inside the Town Bahia. O thought Requião was imbued not only of Allan Kardec ideas, their reviewers, Jean-Baptiste Roustaing, Pietro Ubaldi and Osvaldo Polidoro and Chico Xavier, authors discussed the supposed scientific aspect of the doctrine the example of Ernesto Bozzano and Charles Richet, and authors linked to esotericism as Annie Besant.